Perfil hormonal durante o ciclo reprodutivo e reprodução induzida da garoupa verdadeira (Epinephelus marginatus) (Teleostei: Serranidae) em cativeiro - Rodrigues Filho, Jandyr de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Many fish of interest in aquaculture, including the dusky grouper, Epinephelus marginatus exhibit reproductive dysfunctions due to confinement, which in turn affect the hypothalamus-pituitary-gonadal axis that controls the reproductive processes in vertebrates. The aim of this study was to evaluate the profile of gonadal steroids and follicle-stimulating hormone (FSH) throughout the reproductive cycle, during the induced spawning and vitellogenesis induction in E. marginatus females in captivity. During the annual cycle, the concentration of androgens did not change. Moreover, the plasma levels of 17β-estradiol (E2) was significantly higher in the end of the period compared with the initial period of confinement. Plasma concentrations of 17 α-hydroxyprogesterone (17α-OHP) were significantly higher in October, November and January than May, June, July and August, and serum FSH levels were higher in January compared to June, July, August and September, however, the oocytes remained at the stage of primary growth throughout the annual cycle. In the first hormonal induction experiment (non vitellogenic females) only 17α-OHP increased after stimulation with human chorionic gonadotropin (hCG), however this increase was not reflected in the diameter of oocytes and ovulation. In the second experiment, vitellogenic females captured in the natural environment were induced to spawning and ovulated within 24 to 32 hours after the third dose of hCG, showing two different patterns of spawning: the total spawning or spawning in small batches, and plasma levels of E2, testosterone (T) and 17α -OHP presented a progressive increase over the sampling periods. In the experiment with estradiol implants, an increase of this estrogen was observed, but vitellogenesis was not triggered. Finally, we consider that the use of hCG is viable to induce the final maturation and ovulation in vitellogenic females and we suggest a period of about 3 years of ...

Muitos peixes de interesse na aquicultura, dentre eles a garoupa-verdadeira, Epinephelus marginatus, exibem disfunções reprodutivas devido ao confinamento, que por sua vez, afetam o eixo hipotálamo-hipófise-gônadas que controla os processos reprodutivos em vertebrados. O objetivo deste trabalho foi estudar o perfil dos esteroides gonadais e hôrmonio folículo estimulate (FSH) ao longo do ciclo reprodutivo, durante a reprodução induzida e na estimulação da vitelogênese em fêmeas de E. marginatus em cativeiro. Durante o ciclo anual a concentração de andrógenos não se alterou. Por outro lado, o nível plasmático de 17β-estradiol (E2) foi significativamente superior no período final, em comparação com o período inicial de confinamento. Concentrações plasmáticas de 17 α- hidroxiprogesterona (17α-OHP) foram significativamente mais elevadas nos meses de outubro, novembro e janeiro em relação aos meses de maio, junho, julho e agosto, e os níveis de FSH plasmáticos foram superiores em janeiro quando comparados aos meses de junho, julho, agosto e setembro, porém, os ovócitos permaneceram na fase de crescimento primário durante todo o ciclo anual. No primerio experimento de indução hormonal (fêmeas não vitelogênicas) apenas a concentração de 17α-OHP aumentou após a estimulação com gonadotropina coriônica humana (hCG), mas este aumento não se refletiu no diâmetro dos ovócitos e ovulação. No segundo experimento, fêmeas vitelogênicas capturadas no ambiente natural foram induzidas e ovularam no período de 24 a 32 horas após a terceira dose de hCG, apresentando dois padrões diferentes de desova: a desova total ou em pequenos lotes, e os níveis plasmáticos de E2, testosterona (T) e 17α-OHP apresentaram aumento progressivo ao longo dos períodos amostrais. No experimento com implantes de estradiol houve aumento deste estrógeno no plasma, mas sem desencadear a vitelogênese. Por fim, consideramos que...
Keywords: Peixe - Reprodução; Esteroides; Gonadotropinas; Ciclo sexual; Oócitos; Fishes